PEMBENTUKAN KARAKTER RELIGIUS SISWA GENERASI ALPHA MELALUI PROGRAM PEMBIASAAN KEAGAMAAN DI MI ULUMUDDIN JOMBANG - Qori'ah, Maidatul; Muslih, Imam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the formation of religious character among Generation Alpha students through the habituation of Dhuha prayer and Istighosah activities at an Islamic elementary school in Jombang. Generation Alpha, characterized by early exposure to digital technology, faces challenges related to moral and spiritual development in the digital era. Therefore, structured religious habituation programs are considered strategic in strengthening students’ spiritual and moral values. This research employed a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with the principal, teachers, and students, and documentation analysis. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with credibility ensured through triangulation techniques. The findings reveal that: (1) Dhuha prayer and Istighosah are implemented routinely and systematically as part of the school’s religious culture; (2) the formation of religious character occurs through consistent habituation, teacher role modeling, and value reinforcement, fostering discipline, patience, istiqomah, and respectful behavior; and (3) supporting factors include parental involvement and a conducive religious environment, while obstacles involve students’ fluctuating motivation and digital distractions. The study concludes that continuous religious habituation effectively contributes to strengthening the religious character of Generation Alpha students in the context of Islamic elementary education